Transnational Feminist Edutainment Television in Pakistan: Udaari as Case Study. (December 2019) - Malik, Aisha
First created in the context of state-controlled broadcast television of the 1960s, the Urdu serial drama form has proven enduringly popular in Pakistan. This article examines how institutional changes, including the appearance of nongovernmental organisations in this space, have altered the production and reception of these serial dramas and their thematic content, which has recently included such highly charged topics as sexual abuse, harassment and rape. First, I look at how transnationally funded content has impacted modes of production in a liberalised and deregulated Pakistani television industry. Second, I give a case study of the internationally funded drama serial Udaari as an example of agenda setting television intended to create public dialogue and galvanise change, to which I give the name feminist edutainment (FE) that intentionally recalls the form of entertainment education (EE) associated with the work of Miguel Sabido. Finally, I draw on my ethnographic research to argue that contemporary serial dramas, while engaging a domestic reception space primarily occupied by women, have expanded into the online space through the social media activism of feminist influencers.